1997
DOI: 10.1016/s0194-5998(97)70207-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary compromise after use of topical and submucosal α-agonists: possible added complication by the use of β-blocker therapy

Abstract: We report the specifics of 12 cases of severe hypertension after the intraoperative use of topical phenylephrine, submucosal epinephrine, or both. Ten of these 12 patients also developed severe pulmonary edema. Seven of the twelve were treated with beta blockers; 3 of whom suffered cardiac arrest. We propose a common mechanism: the vasoconstrictors caused systemic hypertension, increased left ventricular afterload, decreased left ventricular compliance, and decreased cardiac output. In those patients treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Kalyanaraman et al 1 report a series concerning 12 patients treated with topical phenylephrine and/or submucosally injected epinephrine, perioperative ENT surgery, in previously healthy patients ranging in age from six to 41 yr. The predominant sequence of events reported in that series was consistent with the patient we present, including perioperative hypertension and treatment with a beta-blocker or calcium channel blocker resulting in pulmonary edema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kalyanaraman et al 1 report a series concerning 12 patients treated with topical phenylephrine and/or submucosally injected epinephrine, perioperative ENT surgery, in previously healthy patients ranging in age from six to 41 yr. The predominant sequence of events reported in that series was consistent with the patient we present, including perioperative hypertension and treatment with a beta-blocker or calcium channel blocker resulting in pulmonary edema.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 We present a case of cardiogenic shock following the administration of metoprolol to treat hypertension, (likely) induced by systemic absorption of topical epinephrine used during a routine nasal septoplasty. Written consent for publication was provided by the patient described herein.…”
mentioning
confidence: 99%
“…However, some studies have reported high plasma levels following endobronchial application of epinephrine [71], with significant cardiovascular effects namely acute hypertension and tachyarrythmias [72]. This observation prompted some investigators to use topical antidiuretic hormone derivatives, such as terlipressin and ornipressin, for their vasoconstrictive effect.…”
Section: Management Of Massive Hemoptysismentioning
confidence: 99%
“…These events have been primarily reported in the operative setting and often involve children undergoing otolaryngologic procedures. Reports have further noted an association between β-blocker administration and intranasal vasoconstrictor—induced hypertension (24, 32, 33). …”
Section: Discussionmentioning
confidence: 97%